2017
DOI: 10.1007/s00380-017-1011-6
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of early diastolic intraventricular pressure gradient in the left ventricle among patients with repaired tetralogy of Fallot

Abstract: Assessment of left ventricular (LV) dysfunction is vital in patients with repaired tetralogy of Fallot (rTOF). The early diastolic intraventricular pressure gradient (IVPG) in the LV plays an important role in diastolic function. IVPG is calculated as the intraventricular pressure difference divided by the LV length, which allows to account for differences in LV size and therefore calculate IVPG in children. We aimed to investigate the mechanisms of LV diastolic dysfunction by measuring mid-to-apical IVPG as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 32 publications
1
16
0
Order By: Relevance
“…Our findings support and expand upon a small number of previously published works, mostly using speckle-tracking echocardiography [ 20 , 21 , 24 31 , 47 ] and a couple using CMR [ 23 , 48 ], that have shown that rotational mechanics are impaired in rTOF. Several studies found that abnormalities in basal rotation were predominantly driving the impairment in torsion [ 20 , 23 , 26 , 29 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our findings support and expand upon a small number of previously published works, mostly using speckle-tracking echocardiography [ 20 , 21 , 24 31 , 47 ] and a couple using CMR [ 23 , 48 ], that have shown that rotational mechanics are impaired in rTOF. Several studies found that abnormalities in basal rotation were predominantly driving the impairment in torsion [ 20 , 23 , 26 , 29 ].…”
Section: Discussionsupporting
confidence: 90%
“…More advanced measures of LV myocardial mechanics such as deformation, synchrony, and rotational mechanics may be more sensitive markers of LV dysfunction [ 18 23 ]. Rotational mechanics, such as twist and torsion, have been less well studied, but prior reports have indicated that these measures are abnormal in rTOF patients [ 20 , 24 31 ], and are associated with adverse outcomes [ 21 ]. Most of these studies used echocardiography to measure rotational parameters which may be technically limited by reduced acoustic windows, particularly in post-operative patients.…”
Section: Introductionmentioning
confidence: 99%
“…Intraventricular pressure gradient (IVPG). IVPD was calculated using in-house code written in MATLAB (The MathWorks, Natick, MA) as previously described 13 . Briefly, for the analysis of IVPG, color M-mode apical four chamber views were stored.…”
Section: Methodsmentioning
confidence: 99%
“…IVPG was calculated by dividing the IVPD by the LVL. To evaluate the segmental pressure difference of each part of the heart, the left ventricle was trisected as previously described 13 . The apical side of the heart was named "apical", the middle part was named "mid", and the basal part was named "basal".…”
Section: Methodsmentioning
confidence: 99%
“…The total IVPD was further separated into the basal and mid and apical segments (hereafter, basal and apical segments), as previously described (Figure 2). 8 Furthermore, to overcome differences in LV size, we calculated the IVPG as IVPD/LV length. 8-10, 21 The basal segment was defined as one-third of the total LV length from the mitral valve, whereas the apical segment was defined as the remaining two-thirds.…”
Section: Myocardial Layer-specific Strain On 2dstmentioning
confidence: 99%